Serum Neuroinflammatory Disease-Induced Central Nervous System Proteins Predict Clinical Onset of Experimental Autoimmune Encephalomyelitis - Raphael, Itay; Webb, Johanna; Gomez-Rivera, Francisco; Chase Huizar, Carol A.; Gupta, Rishein; Arulanandam, Bernard P.; Wang, Yufeng; Haskins, William E.; Forsthuber, Thomas G. (Frontiers in Immunology, 2017)
There is an urgent need in multiple sclerosis (MS) patients to develop biomarkers and laboratory tests to improve early diagnosis, predict clinical relapses, and optimize treatment responses. In healthy individuals, the transport of proteins across the blood-brain barrier (BBB) is tightly regulated; whereas, in MS, CNS inflammation results in damage to neuronal tissues, disruption of BBB integrity, and potential release of neuroinflammatory disease-induced CNS proteins (NDICPs) into CSF and serum. Therefore, changes in serum NDICP abundance could serve as biomarkers of MS. Here we sought to determine if changes in serum NDICPs are detectible prior to clinical onset of experimental autoimmune encephalomyelitis (EAE), and therefore enable prediction of disease onset. Importantly, we show in longitudinal serum specimens from individual mice with EAE, that pre-onset expression waves of SYN2, GS, ENO2, and SYT1 enable prediction of clinical disease with high sensitivity and specificity. Moreover, we observed differences in serum NDICPs between active and passive immunization in EAE, suggested hitherto not appreciated differences for disease induction mechanisms. Our studies provide the first evidence for enabling the prediction of clinical disease using serum NDICPs. The results provide proof-of-concept for the development of high-confidence serum NDICP expression waves and protein biomarker candidates for MS.